Kelayakan Media Pembelajaran Praktikum Fisika Teknik Mengunakan Video Tutorial di AIKOM Ternate - Susanti H. Hasan; Laroma Larumbia (Universitas Hamzanwadi, 2021)
The Covid-19 emergency period requires the implementation of online learning, which was previously carried out offline. This condition causes engineering physics lectures to experience problems in the practical process. For this reason, the purpose of this research is to make learning media that is feasible and simple and easily accessible (YouTube) in the form of video tutorials on engineering physics practicum. The method used is RD with ADDIE model consisting of Analysis, Design, Development, Implementation and Evaluate stages. Data collection techniques using Likert scale questionnaires and analyzed using quantitative descriptive techniques. The results showed that the practicum learning this product video tutorials was declared very-suitable (VS) for use by media experts with a percentage of 92.5% and according to material experts, it was stated to be very-feasible (VF) with a percentage of 85%, and the results of user responses were stated to be VF with a percentage of 86.20%. So that online practicum applies this media is very suitable to be implemented as a practicum learning media.